Molecular designing and Virtual Screening Based Drug design for MABA Enzyme of Mycobacterium Tuberculosis - Debashis Panda, Abhishek Chowdhury, Monjur Ahmed Laskar, Manabendra Dutta Choudhury (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Computer Aided Drug Designing of the NAP binding site of MabA enzymes. Methodology: Mycobacterium tuberculosis causes global infectious disease tuberculosis, which has remained among the top 10 causes of death worldwide. The emerged multidrug-resistant TB (MDR TB) and extensively drug-resistant TB (XDR TB) makes this problem more complex. β-ketoacyl-ACP reductase (MabA), a member of the type-II fatty acid elongation system (FAS-II) is primarily involved in the creation of very long chain fatty acid derivatives. These derivatives are essential precursors for mycolic acids, primary constituents of M. tuberculosis cell wall. Here we have adopted the computational approach followed by ligand molecular modelling, ligand screening, virtual screening and binding pattern analysis in search of potential new lead compounds for Mycobacterium tuberculosis MabA protein. Results: The ligands were screened using an integrated computational protocol that relies on virtual screening and ADMET analysis methods. In this study, we found two compounds, i.e., Compound a1 and a2, which showed the highest binding energy and established the hydrogen bond with the MabA enzyme. Conclusion: Computer Aided Drug Designing approach revealed that two compounds (a1 and a2) had the potential to interact with the NAP binding site of MabA enzymes. Keywords: β-ketoacyl-ACP reductase, MabA, Computer Aided Drug Designing, ADMET